Comparisons of laser and laser-arc hybrid welded carbon steel with beam oscillation. (January 2023) - Hao, Kangda; Gao, Zhiyuan; Huang, Junwei; Xu, Lianyong; Liu, Youqing; Han, Yongdian; Zhao, Lei; Ren, Wenjin
Highlights: Laser welding and laser-arc hybrid welding with beam oscillation were carried out. The width variation of HAZ was opposite in oscillating laser and hybrid welding. The variation in HAZ width was illustrated according to the heat distribution. The elongation rate was improved while the hardness decreased by oscillation. Relation of microstructure and mechanical properties was established. Abstract: Laser welding and laser-arc hybrid welding of Q235 steel with and without beam oscillation were carried out, the weld formation, microstructure and mechanical properties were investigated. It was found that the width of the heat affected zone (HAZ) increased by beam oscillation during laser welding, while decreased during laser-arc hybrid welding. The side-plate ferrite (FS) increased by the beam oscillation, while the blocky ferrite (FB) was broken up and the proeutectoid ferrite (FP ) was reduced. Moreover, the beam oscillation was beneficial to improve the elongation rate from 6.8% to 7.6% for laser welds and 8.3% to 9.8% for hybrid welds, while decrease the micro-hardness of the welds by 85 HV10 for the laser welds and 10 HV10 for the hybrid welds. Finally, the variation in width of HAZ was illustrated according to the heat distribution of the laser source, arc column and oscillating behavior of the laser beam. The relation between microstructure and mechanical properties was established, according to the stirring effect of the oscillated laser beam within the molten pool, and the solidification theories.